Effects of visfatin on brown adipose tissue energy regulation using T37i cells. (January 2019) - Dimitriadis, Georgios K.; Adya, Raghu; Tan, Bee K.; Jones, Terence A.; Menon, Vinod S.; Ramanjaneya, Manjunath; Kaltsas, Gregory; Miras, Alexander D.; Randeva, Harpal S.
Highlights: Visfatin and leptin influence brown pre-adipocyte thermogenesis dependent of dose. At physiological levels, visfatin and leptin increased uncoupling protein-1 (UCP-1). High concentrations of both visfatin and leptin decreased UCP-1 protein levels. Visfatin is raised in obesity. Obesity causes decreased BAT activity, plausibly through reduced UCP-1 levels. Abstract: The role of brown adipose tissue (BAT) in pathological states of energy homeostasis and impaired adipocyte function, such as obesity has been a major area of research interest in recent years. Herein, we sought to determine the direct effects of adipokines, visfatin and leptin on BAT thermogenesis. The effects of mouse recombinant visfatin, nicotinamide mononucleotide (NMN) and leptin with or without FK866 were studied on differentiated T37i cells. Treated cells were analyzed for key genes and proteins regulating BAT [UCP-1, PRD1-BF1-RIZ1 homologous domain-containing 16 (PRDM-16), PPARgamma-coactivator-1alpha (PGC-1α) and receptor-interacting protein 140 (RIP-140)] using quantitative PCR and western blot analysis. Data is presented as mean P -values. Both visfatin and leptin had significant concentration dependent effects on thermogenesis in brown pre-adipocytes and at physiological levels, increased uncoupling protein-1 (UCP-1) levels in brown adipocytes. These effects of visfatin were similar to that of nicotinamide mononucleotide (NMN), further strengthening the enzymatic role of visfatin. We also showed that leptin induced UCP-1 mRNA expression and protein production appears to be mediated by visfatin. High concentrations of both visfatin and leptin led to a dramatic decrease in UCP-1 protein levels, supporting the notion that visfatin levels are raised in obesity and that obese people have reduced BAT activity, plausibly through a reduction in UCP-1 levels. Additionally, we found differential regulation of key brown adipogenic genes, specifically, PRD1-BF1-RIZ1 homologous domain-containing 16 (PRDM-16), PPARgamma-coactivator-1alpha (PGC-1α) and receptor-interacting protein 140 (RIP-140) by visfatin. Our observations provide novel insights in the potential actions of visfatin in BAT.